ANALISIS NOSIBAGI PENGOLAHAN KAPUK DALAM TINJAUAN HUKUM ISLAM DI DESA DALAKA KECAMATAN SINDUE - Enik Tresnifah Bte Amir (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
This thesis is entitled Nosibagi Analysis of Kapuk Processing in Islamic Law Review in Dalaka Village, Sindue Subdistrict, by stating the main problem, How is the analysis of the Nosibagi kapok processing in Dalaka Village, Sindue District and how Islamic law reviews the Nosibagi system for kapok processing in Dalaka Village, Sindue District The method uses qualitative methods with data and data observation approaches starting from the beginning, where the author sees and analyzes things that are pleasing to the required data, especially Nosibagi (profit sharing) processing of kapok in Dalaka Village, Sindue District. Based on the results of the study, it shows that, First, the Nosibagi analysis of kapok processing in Dalaka Village, Sindue Subdistrict, is carried out orally among the parties concerned, with the provision of mutual trust with each other with a 50/50% share, including the owner of the capital and the manager. Second, in the review of Islamic law, this division prioritizes the value of justice for the parties concerned, where the owner of the capital does not take all of his shares if the sales of cotton mattresses and pillows are lacking, and the owner of the capital gives bonuses to managers in order to get more results. Managers, it is better to maintain the level of fairness in the distribution of the results of kapok processing which can be developed downward. Even though the agreement was made orally. It is hoped that the Government will pay more attention to the business of kapok processing so that the agreement is carried out well, as well as provide training on how to share good results according to Islamic law.